The trajectory of COVID-19 pandemic and handwashing adherence: findings from 14 countries - Szczuka, Zofia (2022)
The COVID-19 pandemic has affected people's engagement in health behaviors, especially those that protect individuals from SARS-CoV-2 transmission, such as handwashing/sanitizing. This study investigated whether adherence to the World Health Organization's (WHO) handwashing guidelines (the outcome variable) was associated with the trajectory of the COVID-19 pandemic, as measured by the following 6 indicators: (i) the number of new cases of COVID-19 morbidity/mortality (a country-level mean calculated for the 14 days prior to data collection), (ii) total cases of COVID-19 morbidity/mortality accumulated since the onset of the pandemic, and (iii) changes in recent cases of COVID-19 morbidity/mortality (a difference between country-level COVID-19 morbidity/mortality in the previous 14 days compared to cases recorded 14-28 days earlier).